ESP Students Perceptions on the Use of Whatsapp Application as a Learning Tool - Palupi*, Dian; Novia Bahari, Jannatul Laily; Wulandari, Rizka Maulina (Riwayat: Educational Journal of History and Humanities, 2023)
The development of technology provides a huge impact on the educational setting which increasing Mobile-Assisted Language Learning (MALL) usage especially in supporting ESP students. One of the mobile applications used in supporting language learning is WhatsApp Messenger. This study aimed to investigate ESP students perceptions on the use of WhatsApp in English language learning. The research approach was a descriptive quantitative approach while the design of this research was a survey. The participants were 22 male ESP students who followed the English class held by Helutrans Art-moving Company. For collecting the data, the researcher employed a questionnaire adapted from Mistar Embi (2016). The questionnaire consisted of three parts such as the attitude towards WhatsApp, the usefulness of WhatsApp and also the constraint in using WhatsApp. In analyzing the data, it applied descriptive statistics using SPSS version 26 in the form of frequencies, means, and standard deviations. The findings of the research revealed that the majority of the research participants had positive perceptions concerning the use of WhatsApp in the ESP setting. It implied that ESP students agreed for using WhatsApp on language learning was easy, useful and effective in increasing their motivation, interest, confidence, and their activeness. They also felt that using WhatsApp could increase their English skill such as listening, reading, writing and speaking.